Informe 100 días de régimen de excepción en El Salvador - Cruz Molina, Jacqueline Natalia; Ponce Rubio, Natalia (Investigaciones UCA, 2022)
No hay resúmenes disponibles. Investigaciones UCA, Año. 2, Vol. 2, 2021-2022: 181-184.